Embarazada adolescente con hemorragia en el tercer trimestre más placenta previa total - Salvatierra Campos, Geomayra Katherine (2018)
Introduction: Hemorrhage in the third trimester of pregnancy is considered to be an illness that implies an increase in the danger that can be defined or defined by life, the health of the mother, fetus or the child during the neonatal period. . As a rule, the bleeding during the pregnancy is divided into two groups: The haemorrhages that occur during the first half of gestation, the main reasons are: abortion , threat of a bortion, ectopic embarrassment and trophoblastic disease. Conclusion: The present case study concludes that placenta previa plus hemorrhage is very frequent in adolescent patients in which the risks of maternal-fetal complications allow the act of nursing at an early stage, when applying the physical examination complying with all the aspects of assessment, determining the dysfunctionality of the patterns whose purpose is to prioritize nursing activities and apply them in order to restore the state of health of the mother and child binomial.